2021
DOI: 10.1093/jnci/djab102
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mendelian Randomization Studies in Deciphering the Effect of Obesity on Cancer

Abstract: Associations of obesity have been established for at least 11 cancer sites in observational studies, though some questions remain as to causality, strength of associations, and timing of associations throughout the life course. In recent years, Mendelian randomization (MR) has provided complementary information to traditional approaches, but the validity requires that the genetic instrumental variables be causally related to cancers only mediated by the exposure. We summarize and evaluate existing evidence fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 87 publications
2
35
0
Order By: Relevance
“…For women with overweight in early adulthood, there was instead a reduced risk of postmenopausal breast cancer, independent of later weight-gain. For women who did gain weight after early adulthood, especially leaner women, there was instead an increased risk of receptor positive breast cancer [ 4 , 29 ], which has been further validated in a recent Mendelian Randomization study [ 8 ]. Some studies have also suggested that the positive association between obesity and postmenopausal breast cancer is more pronounced in older postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For women with overweight in early adulthood, there was instead a reduced risk of postmenopausal breast cancer, independent of later weight-gain. For women who did gain weight after early adulthood, especially leaner women, there was instead an increased risk of receptor positive breast cancer [ 4 , 29 ], which has been further validated in a recent Mendelian Randomization study [ 8 ]. Some studies have also suggested that the positive association between obesity and postmenopausal breast cancer is more pronounced in older postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have identified associations with tumor angiogenesis, and an increase in proinflammatory cytokines promoting tumor growth, invasion, and metastatic potential [3]. For breast cancer, most earlier studies have found an association between obesity and risk of postmenopausal breast cancer [4][5][6][7], even though recent publications have modified the picture and suggested that the risk may be limited to women with adulthood overweight, and especially postmenopausal weight-gain, and not to women who have been overweight from childhood, as childhood overweight seems to exert a protective effect against breast cancer risk [8]. The association between specific tumor types and in overweight/obese women is, however, less clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Residual confounding by smoking may also contribute to underestimation of the impacts of excess adiposity; for example, high body weight is strongly associated with lower risk of lung cancer, but there is no plausible mechanism and Mendelian randomization analyses suggest that this inverse association is not causal. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Evidence from mendelian randomisation studies reinforced causal relationships with cancers of the colorectum, endometrium, ovary, kidney, pancreas and oesophagus (adenocarcinoma) but similarly could not confirm causality for gallbladder cancer, gastric cardia cancer, and multiple myeloma, citing low power of the included studies. 35 …”
Section: Discussionmentioning
confidence: 99%